PENGARUH BODY IMAGE DAN PENGETAHUAN TENTANG STUNTING TERHADAP KEJADIAN ANEMIA PADA REMAJA PUTRI DI DESA MATANG SEULIMENG KECAMATAN LANGSA BARAT KOTA LANGSA - Lina Lina; Supriyanti; Eva Sulistany (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2022)
Anemia is the most common medical problem in the world, especially in developing countries. Adolescent girls are one of the groups that are prone to anemia. The target of the anemia prevention program has been developed to reach young women as a strategic effort in an effort to break the knot of nutritional problems. This study aims to determine the effect of body image and knowledge of stunting on the incidence of anemia in adolescent girls in Matang Seulimeng Village, Langsa City in 2021. This type of research is quantitative with a Cross Sectional approach. The population in this study were young women in Matang Seulimeng Village, Langsa City with a total sample of 62 people. Bivariate analysis using Chi Square test. The results showed that there was a significant relationship between body image and the incidence of anemia in young women in Matang Seulimeng Village, Langsa City with a p value = 0.01, there was a significant relationship between knowledge of stunting and the incidence of anemia in young women in Matang Seulimeng Village, Langsa City with a value of p value = 0.048. It is hoped that the health office, puskesmas, community nurses and village midwives will provide counseling about anemia in adolescent girls and prevention of stunting from an early age.